Breast cancer management in Australian rural indigenous women: trends and challenges - Clement, Zackariah V. K. (International Journal Of Community Medicine And Public Health, 2017)
Cancer patients residing in Australian rural areas have a 7% higher mortality when compared to their counterparts in urban centres. Close to half of the indigenous Australians reside in regional and remote areas. Despite of the lower incidence rates among the indigenous women, and increase in overall breast screen participation indigenous women have lower participation rates when compared to non-indigenous women and the mortality from breast cancer is similar in both groups. Due to their relative the indigenous women with breast cancer living in the rural and regional Australia face several barriers and challenges. Although there is no perfect algorithm to address this problem, government should provide adequate specialist, allied health and support services to the patient’s rural and regional areas and this should not be any different to the services offered to their urban counterparts. A multidisciplinary approach should be taken to the management of breast cancer for all indigenous women in the rural areas. Outreach clinics and Tele-oncology can overcome some of the challenges of access. Health professionals should also be trained in culturally sensitive and effective communication strategies to improve interpersonal relationship, trust, compliance and overall patient outcomes.